(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
The work focuses on Exploring African Folklores and Oral Tradition in Indigenous Religion. Data for this study were collected from two major sources, my own personal experience as participant observer, in addition to my own personal experience, I made use of oral interviews and secondary sources. The methodology adopted in the analysis of data is phenomenological approach. The findings show that African folklores and oral tradition is established not only between the living and the dead but reveals that there is a synergy between the physical world and spiritual world. It further unveils that there is a system of narrative and communication of oral traditional in Africa. The study concludes that Oral transmission of religious teachings in African traditional societies relies on a combination of storytelling, ritual performances, proverbs, songs, and community participation. The study recommends that African Folklores and Oral Tradition should be incorporated into the educational curriculum in Nigerian schools, that African traditional stories, songs, and proverbs be documented and digitized, communities should be encouraged to organize storytelling workshops and festivals that celebrate African oral traditions. Traditional religious leaders, cultural organizations, and government agencies should collaborate to promote the significance of oral traditions in preserving African traditional religion and by sharing African stories and religious teachings with international audiences, the richness of African heritage can be showcased, and these traditions can be recognized as valuable assets in the global cultural landscape.